INTEREST RATES AND MEMBER SAVINGS IN COOPERATIVE CREDIT PROVISION AT SMP 1 SAMPOLAWA - Nurfita Nurfita; Ernawati Malik; I Wayan Sujana (JIEM : Journal Of International Entrepreneurship And Management, 2026)
This study aims to analyze the management of interest rates and member savings in credit distribution at the Savings and Loan Cooperative of SMP Negeri 1 Sampolawa. The research uses a qualitative method with data collection techniques including observation, interviews, documentation, and literature study. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that interest rate management is carried out through planning, determination, and implementation stages in a participatory manner. The applied policy is able to encourage members’ interest in borrowing. Member savings management, consisting of principal, mandatory, and voluntary savings, functions as the main source of cooperative capital and is supported by proper recording and supervision systems. In addition, credit distribution is carried out by considering members’ repayment capacity and applying prudential principles. Overall, there is a relationship between interest rates, member savings, and credit distribution in supporting cooperative performance.